The impact of coronavirus (COVID-19) related public-health measures on training behaviours of individuals previously participating in resistance training: a cross-sectional survey study - Steele, J.; Androulakis-Korakakis, P.; Carlson, L.; Williams, D.; Phillips, S.; Smith, D.; Schoenfeld, B. J.; Loenneke, J. P.; Winett, R.; Abe, T.; Dufour, S.; Franchi, M. V.; et al. (Sports Medicine, 2021)
Introduction: Understanding the impact of lockdown upon resistance training (RT), and how people adapted their RT behaviours, has implications for strategies to maintain engagement in similar positive health behaviours. Further, doing so will provide a baseline for investigation of the long-term effects of these public health measures upon behaviours and perceptions, and facilitate future follow-up study. Objectives: To determine how the onset of coronavirus (COVID-19), and associated `lockdown`, affected RT behaviours, in addition to motivation, perceived effectiveness, enjoyment, and intent to continue, in those who regularly performed RT prior to the pandemic. Methods: We conducted an observational, cross-sectional study using online surveys in multiple languages (English, Danish, French, German, Italian, Portuguese, Slovakian, Swedish, and Japanese) distributed across social media platforms and through authors` professional and personal networks. Adults (n = 5389; median age = 31 years [interquartile range (IQR) = 25, 38]), previously engaged in RT prior to lockdown (median prior RT experience = 7 years [IQR = 4, 12]) participated. Outcomes were self-reported RT behaviours including: continuation of RT during lockdown, location of RT, purchase of specific equipment for RT, method of training, full-body or split routine, types of training, repetition ranges, exercise number, set volumes (per exercise and muscle group), weekly frequency of training, perception of effort, whether training was planned/recorded, time of day, and training goals. Secondary outcomes included motivation, perceived effectiveness, enjoyment, and intent to continue RT. Results: A majority of individuals (82.8%) maintained participation in RT during-lockdown. Marginal probabilities from generalised linear models and generalised estimating equations for RT behaviours were largely similar from pre- to during-lockdown. There was reduced probability of training in privately owned gyms (~ 59% to ~ 7%) and increased probability of training at home (~ 18% to ~ 89%); greater probability of training using a full-body routine (~ 38% to ~ 51%); reduced probability of resistance machines (~ 66% to ~ 13%) and free weight use (~ 96% to ~ 81%), and increased probability of bodyweight training (~ 62% to ~ 82%); reduced probability of moderate repetition ranges (~ 62-82% to ~ 55-66%) and greater probability of higher repetition ranges (~ 27% to ~ 49%); and moderate reduction in the perception of effort experienced during-training (r = 0.31). Further, individuals were slightly less likely to plan or record training during lockdown and many changed their training goals. Additionally, perceived effectiveness, enjoyment, and likelihood of continuing current training were all lower during-lockdown. Conclusions: Those engaged in RT prior to lockdown these behaviours with only slight adaptations in both location and types of training performed. However, people employed less effort, had lower motivation, and perceived training as less effective and enjoyable, reporting their likelihood of continuing current training was similar or lower than pre-lockdown. These results have implications for strategies to maintain engagement in positive health behaviours such as RT during-restrictive pandemic-related public health measures.